Analisis Penggunaan Media Pembelajaran Dinding Kata (Word Wall) untuk Meningkatkan Pemahaman Siswa pada Pembelajaran Bahasa Inggris Materi Parts of the Body - Nanda Ramadani; Neha Divya; Nurul Tri Ashayudha Br Matondang; Erlina Ramadhani; Sofia Simangunsong; Daniel Sinaga (Lembaga Pengembangan Kinerja Dosen, 2025)
This study analyzes the effectiveness of using Word Wall as a learning medium to enhance student’s understanding in English language learning, particularly on the topic of parts of the body. A Word Wall is a visual medium consisting of a collection of specific words displayed on a large wall or board in the classroom, helping students recognize, memorize, and understand vocabulary interactively. This research employs a descriptive qualitative method with a literature review approach, collecting and analyzing various relevant sources. The results indicate that Word Walls are effective in improving student’s vocabulary mastery, which is a crucial component of English language learning. Students using this medium showed increased activity, enthusiasm, and confidence in practicing speaking. Additionally, post-test scores were consistently higher than pre-test scores, indicating significant improvement in understanding. This medium also enhanced students' learning outcomes, with the percentage of learning completeness increasing from the first to the final cycle in several classroom action research studies. Thus, Word Walls prove to be an effective and engaging learning medium for improving students' understanding and learning outcomes in English language education.